STEM-Robotics Training for Science Teachers: Designing Interactive Learning - Muliyati, Dewi; Wini Sholina; Vina Dwi Cahyani; Nisrina Tsabitah Zain; Putri Marsha Sabrina; Fauzi Bakri; Handjoko Permana; Dwi Handarini; Rahmah Purwahida; Muhammad Suryauno Mahmudah (Mitra Teras: Jurnal Terapan Pengabdian Masyarakat, 2024)
STEM education is critical in current teaching because it combines science, technology, engineering, and mathematics into a unified learning experience. STEM education focuses on educating students for the changing profession by developing critical thinking and problem-solving abilities while also addressing gender inequalities in STEM disciplines. Robotics, an important component of STEM education, provides hands-on learning experiences that pique students' curiosity and practical application of STEM principles. To overcome the scarcity of talented individuals in STEM industries, educators must get STEM and robotics training. This publication describes a STEM-Robotics training program meant to help science instructors incorporate robotics into their teaching techniques. The program seeks to improve instructors' robotics education skills, create new teaching techniques, bridge theory and practice, and improve student engagement and learning results. By combining hands-on robotics activities into the curriculum, the program hopes to foster dynamic learning settings that encourage creativity, critical thinking, and collaborative problem-solving abilities. This book describes the STEM-Robotics training program's rationale, organization, aims, and expected impact, emphasizing its importance in educating students for future employment in technology, engineering, and other STEM-related disciplines.